Across the waves: a bibliometric analysis of container shipping research since the 1960s. Issue 6 (18th August 2017) - Lau, Yui-yip; Ducruet, César; Ng, Adolf K. Y.; Fu, Xiaowen
ABSTRACT: The paper investigates collaborative and semantic patterns that emerged between 1967 and 2013 about the theme of container shipping based on a corpus of 294 articles published in scholarly journals within the fields of transportation, supply chain, economics, geography, regional planning and development, and operations research. An analysis based on the co-occurrence of title words allows identifying dominant sub-themes and their evolution. Main results point to the gradual diversification of container shipping research, from the dominance of economics towards a more trans-disciplinary set of approaches which integrate port-related activities and multimodal networks. Yet, disciplinary specialization remains strong up to nowadays so that container shipping research remains rather fragmented. While co-authorships have increased over time, they remain polarized by few, weakly connected research battalions. Our study suggests that research on container shipping would benefit from more frequent contacts between such communities to foster in-depth cross-disciplinary studies and fundamental cooperation.